[Retracted] Meaning, Message, and Rhetoric in Kitabisa.com Advertisement - Luh Eka Candra Yulika, Ni; Wayan Budiarta, I; Gusti Ayu Agung Dian Susanthi, I (KnE Social Sciences, 2022)
RETRACTION NOTICE: Owing to a miscommunication between the co-authors, this article was submitted and accepted by two publications. After realising the error, the authors requested that this version of the article be retracted.